Important Entrepreneurial Characteristics to Survive in the Covid-19 Pandemic Era (Case Study on Alumni Business Administration Program of Atma Jaya Catholic University of Indonesia) - Ati Cahayani; Aristo Surya Gunawan (ADI Publisher, 2020)
This Covid-19 pandemic era not only caused problems in the health sector but also in the economic sector. Indonesia's neighbouring country, has entered a recession. We have not yet entered a recession, but it seems unavoidable. One important thing that is expected to support national economic resilience from recession is entrepreneurs, especially the MSMEs entrepreneurs. This study will analyze the essential characteristics possessed by six alumni of the Business Administration Program, Atma Jaya Catholic University of Indonesia, who are MSMEs entrepreneurs. The main concept used in this study is the entrepreneurial characteristics from Longenecker and Hornaday. The research method used is qualitative with descriptive data analysis techniques. Researchers used convenience technique sampling and used the first data source by interviewing informant and secondary data sources about informant business activity. The conclusion from this research is that the six informants have the entrepreneurial characteristics from Longenecker.